Low-carbon city construction and corporate carbon reduction performance: evidence from a quasi-natural experiment in China - Chen, Shaojian (Journal of business ethics, 2022)
Enterprises are the market players for carbon reductions and carbon trading, and they are also the significant driving force in a low-carbon economy and society. Using the data of A-share listed companies from 2010 to 2016, this study uses a difference-in-differences (DID) model to examine the effects of the low-carbon city construction on corporate carbon reduction performance. Consistent with our hypotheses, we find that the low-carbon city construction promotes corporate carbon reduction performance. Further analysis indicates that the policy effect is stronger for state-owned enterprises (SOEs) than non-state-owned enterprises (non-SOEs). Moreover, environmental quality can affect the promotion of local government officials, which is more prominent in pilot low-carbon cities, and political promotion incentives significantly improve corporate carbon reduction performance. Furthermore, the highest emission reduction effects come in the fourth year after adopting a carbon reduction policy and are concentrated among the firms in the eastern region. Overall, our findings offer a new point view for a deeper understanding of the improvement of corporate carbon reduction performance, and provide microscopic evidence for the objective evaluation of the environmental effects of China's low-carbon city pilot policies.